2018
DOI: 10.1016/j.jmmm.2017.04.074
|View full text |Cite
|
Sign up to set email alerts
|

Creation, transport and detection of imprinted magnetic solitons stabilized by spin-polarized current

Abstract: With the recent proposition of skyrmion utilization in racetrack memories at room temperature, skyrmionics has become a very attractive field. However, for the stability of skyrmions, it is essential to incorporate the Dzyaloshinskii-Moriya interaction (DMI) and the out-of-plane magnetic field into the system. In this work, we explore a system without these interactions. First, we propose a controlled way for the creation of magnetic skyrmions and skyrmioniums imprinted on a ferromagnetic nanotrack via a nanop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…As the skyrmionium has a zero skyrmion number, it is immune from the SkHE and can be used to reliably delivery information in narrow and long nanotracks. Recently theoretical and simulation works have demonstrated that both spin currents and spin waves are able to drive skyrmioniums into motion in narrow nanotracks [174,229,230,232]. In 2018, Zhang et al [231] realized the real-space observation of a skyrmionium in ferromagnetic thin films coupled to a magnetic topological insulator [see Fig.…”
Section: Information Storage: Racetrack Memory and Skyrmion-mtjmentioning
confidence: 99%
“…As the skyrmionium has a zero skyrmion number, it is immune from the SkHE and can be used to reliably delivery information in narrow and long nanotracks. Recently theoretical and simulation works have demonstrated that both spin currents and spin waves are able to drive skyrmioniums into motion in narrow nanotracks [174,229,230,232]. In 2018, Zhang et al [231] realized the real-space observation of a skyrmionium in ferromagnetic thin films coupled to a magnetic topological insulator [see Fig.…”
Section: Information Storage: Racetrack Memory and Skyrmion-mtjmentioning
confidence: 99%
“…Skyrmionium can be moved inside a nanotrack by spin waves 61 , 62 , magnetic field gradient 31 , 33 and spin-polarized current 32 , 34 , 63 . In this section, we demonstrate the spin current-dependent dynamics of a skyrmionium in comparison with a skyrmion and analyze the skyrmionium stability under the current action.…”
Section: Spin Current Driven Motion Of Skyrmioniummentioning
confidence: 99%
“…Recently, it was experimentally observed magnetic skyrmions in ferrimagnetic GdFeCo films [14] which have similar structures to antiferromagnets. It has been also claimed that a suitable spinpolarized current (SPC) could induce the appearance of AFM skyrmions [13] and that they could move for very long distances parallel to such a current [15][16][17], making them feasible information carriers for technological skyrmion-based devices. In this sense, it was shown that skyrmions lying in AFM thin disks are promising candidates to a new generation microwave signal generators [18].…”
Section: Introductionmentioning
confidence: 99%